How Do Gender Quotas Affect Workplace Relationships? Complementary Evidence from a Representative Survey and Labor Market Experiments - Ip, Edwin; Leibbrandt, Andreas; Vecci, Joseph (Management Science, 2020)
Gender quotas are frequently proposed to address persistent gender imbalances in managerial roles. However, it is unclear how quotas for female managers affect organizations and whether quotas improve or damage relationships between managers and their subordinates. We conduct a representative survey to study opinions on quotas for female managers and, based upon the survey, design a novel set of experiments to investigate how quotas influence wage setting and effort provision. Our findings reveal that both opinions about gender quotas and workplace behavior crucially depend on the workplace environment. In our survey, we observe that approval for gender quotas is low if women are not disadvantaged in the manager-selection process, regardless of whether there are gender differences in performance. Complementing this evidence, we observe in our experiments that quotas lead to lower effort levels and lower wages in such environments. By contrast, in environments in which women are disadvantaged in the selection process, we observe a higher approval of quotas as well as higher effort levels and higher wages. These findings are consistent with the concept of meritocracy and suggest that it is important to evaluate the perception of gender disadvantages in the workplace environment before implementing quotas. This paper was accepted by Axel Ockenfels, decision analysis.